HUBUNGAN ANTARA PELAYANAN DAN KETEPATAN FITTING PADA PEMAKAI KACAMATA TERHADAP KEPUASAN PASIEN - Hanafiah, Hanafiah; Husin, Omar Davis (JURNAL KESEHATAN TERAPAN, 2021)
Background: In order to meet the demands of optical refraction or optometry services in health care facilities, service standards are needed so that optical refraction or optometry services in every health care facility have uniformity, quality and can be accounted for. Methods: This analytical survey research with a cross sectional approach was conducted in 2019 with a minimum sample size of 52 people using a simple random sampling technique. Data obtained through interviews using a questionnaire and analyzed univariate and bivariate using SPSS ver 25.0. Results: There is a significant relationship between service and the accuracy of eyeglass fittings with patient satisfaction (p value = 0.008). Conclusion: There is a significant relationship between service and the accuracy of eyeglass fittings with patient satisfaction. This can be used as input for developing health services. Keywords: Eyeglass Fitting Accuracy, Patient Satisfaction, Service